The Judge's Ratio Decidendi in Rejecting A Claim for Past Child Support (A Study on the Implementation of SEMA No. 4 of 2016 in Decision No.: 0565/Pdt. G/2023/PA. Bwi) - Saputra, Muhammad Nabil Azizy (Sakina: Journal of Family Studies, 2024)
Divorce poses significant challenges in the division of responsibilities, particularly regarding child support, which impacts their well-being. Negative effects include the loss of family warmth and emotional instability. The Marriage Law emphasizes the obligation of parents to support their children until they become independent, even after the marriage has ended. However, the implementation of child support obligations, especially for basic needs, often encounters legal hurdles, including ambiguity in the amount of support and the application of laws by the courts. This study focuses on the implementation of SEMA Number 4 of 2016 in Decision Number 0565/Pdt.G/2023/PA. Bwi, which rejected a claim for past unpaid child support. The objective is to identify the reasons behind the judge's rejection and evaluate the extent to which the SEMA guidelines are applied. The research employs a normative approach and case study methodology. The findings indicate that the judge denied the claim on the grounds that the obligation for support is of a temporary nature, which contradicts the SEMA guidelines that establish the father’s responsibility for support when the child is in the mother's custody. This rejection reflects the need for a reassessment to ensure that children's rights are effectively protected.